Evaluating the efficacy of subthreshold micropulse laser combined with anti-VEGF drugs in the treatment of diabetic macular edema: a systematic review and meta-analysis - Jiang, Yang; He, Wei; Qi, Shixin (Frontiers in Endocrinology, 2025)
ObjectiveTo compare the clinical efficacy of subthreshold micropulse laser (SML) combined with anti-VEGF drugs versus anti-VEGF drugs monotherapy for diabetic macular edema (DME) through a meta-analysis.MethodsWe systematically reviewed relevant literature from electronic databases and extracted key outcomes, including best corrected visual acuity (BCVA)—comprising ETDRS and LogMAR measures, central macular thickness (CMT), annual frequency of anti-VEGF injections, annual SML applications, and associated complications for both treatment groups at postoperative intervals of 3, 6, 9, and 12 months.ResultsA total of 13 relevant studies were included in this review, including 405 eyes in the experimental group (SML combined with anti-VEGF drugs intravitreal injections) and 400 eyes in the control group (anti-VEGF drugs monotherapy). The results showed no significant difference in ETDRS visual acuity between the two groups at any time point (P > 0.05). However, LogMAR visual acuity significantly improved in the experimental group compared to controls at both 6 and 12 months post-treatment (P < 0.05). Subgroup analysis based on baseline CMT values indicated that patients with baseline CMT < 400 µm had significantly more reduced CMT across all observation points in the experimental group (P < 0.05). Conversely, no significant differences in CMT were found among those with baseline CMT ≥ 400 µm (P > 0.05). Additionally, annual intravitreal injection frequency of anti-VEGF drugs was significantly reduced in the experimental group compared to the controls (P < 0.05). The average numbers of SML applications per year ranged from 1.41 ± 0.37 to 3.4 ± 1.4 times (range: 1–4 times). Common postoperative complications included mild subconjunctival hemorrhage, a light ocular inflammatory reaction, and/or ocular surface discomfort.ConclusionCompared to anti-VEGF drugs monotherapy, combining SML with anti-VEGF drugs can improve visual acuity and reduce macular edema among DME patients—especially those with central macular thickness < 400 µm. The combined approach also reduces anti-VEGF drugs intravitreal injection frequency, and repeated use of SML can alleviate economic burdens on patients.Systematic review registrationhttps://inplasy.com, identifier INPLASY2024120068.